Global Sea Level Rise: Recent Progress and Challenges for the Decade to Come - Josh K. Willis; Don P. Chambers; Chung-Yen Kuo; C.K. Shum (Oceanography, 2010)
The study of sea level rise is a highly interdisciplinary endeavor with important implications for our society as it adapts to a warming climate. Although the past two decades have revolutionized our understanding of sea level rise and its causes (primarily mass input and ocean warming), major scientific challenges must be met before useful predictions can be made. The rate of sea level rise has accelerated considerably relative to the pre-industrial era. Over the twentieth century, global sea level increased at an average rate of about 2 mm yr-1, which is substantially larger than the rate of the previous three millennia. Furthermore, evidence now exists for additional acceleration during the twentieth century. Nevertheless, accurate prediction of future sea level rise requires continued observations as well as significant advances in modeling of the coupled ice-ocean-land-atmosphere climate. A major effort is needed to sustain data recording from satellite altimeters (e.g., the Jason series), from time-variable gravity missions (e.g., Gravity Recovery And Climate Experiment, or GRACE), and from autonomous ocean observing systems (e.g., Argo). In addition, an interdisciplinary research effort is required to address major problems, including improvement of the historical records of sea level rise and ocean warming, the separation of other geophysical processes from sea level rise signals, and a more complete understanding of interactions between the ocean and ice sheets.